THE CONCEPT OF JUSTICE IN THE PERSPECTIVE OF ISLAMIC BUSINESS ETHICS - Aini, Fauqah Nuri; Azzaki , Muhammad Adnan (Neraca: Jurnal Ekonomi, Manajemen dan Akuntansi, 2024)
Islam is not merely a religion but also a way of life that encompasses all aspects of human existence, including business ethics. This study examines the concept of justice from the perspective of Islamic business ethics, emphasizing the importance of justice as the foundation of a fair and sustainable economic system. In Islamic economics, justice is a core principle encompassing wealth distribution, equal treatment, and social responsibility. The research employs a literature review method to analyze relevant sources. The findings reveal that principles such as honesty, transparency, and accountability are essential in fostering business practices that align with Sharia principles. These principles not only promote business success but also yield positive impacts on society and the environment. This study underscores that implementing Islamic business ethics can serve as a solution to address moral challenges in modern business while building a sustainable and socially responsible business model.